Clinico-epidemiological profile of high altitude pulmonary edema - Adhya, Saibal; Menon, Anirudh K.; Bhatnagar, Sharad; Singh, Sanjeev Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: With increase in the footfall to mountainous areas for occupational and recreational purposes, tackling the burden of high-altitude illnesses is a growing public health challenge. High-altitude pulmonary edema (HAPE) is a serious medical condition with peculiar epidemiological characteristics. HAPE is a significant cause of morbidity and mortality among Indian soldiers posted to high-altitude areas. Aims and objectives of the study were to study the common clinical presentation of HAPE among Indian army soldiers and to study the association between induction patterns and acclimatization status with the onset of HAPE. Methods: An observational study was undertaken to study the clinical and epidemiological characteristics of all cases of HAPE from years 2016 to 2019, among Indian army soldiers posted to high-altitude areas in Ladakh. Diagnosis was made by the Lake-Louise consensus criteria. Data was entered in Microsoft Excel and descriptive and inferential statistical tools were applied to test for associations between the variables studied. Results: The overall incidence rate of HAPE was found to be 5.91 per 1,000 soldiers with high frequency among young men. Breathlessness, cough, and headache were the common complaints. 69.45% of cases occurred among men who revisited the mountains after a brief sojourn to the plains. At higher altitudes, incidence rates were higher among acclimatized individuals. Conclusions: HAPE occurs more frequently during the subsequent visits compared to first exposure to high altitude. At extreme altitudes, acclimatization protocols do not confer complete protection against HAPE.